Pengaruh Intellektual Capital, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan - Halimahtussakdiah; Aprila, Rahmi Welsifa (Akuntansi & Ekonomika, 2024)
This study aims to examine the effect of intellectual capital, capital structure, and company size on firm value. The research population consists of 63 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Using a purposive sampling technique, 32 companies were selected as the research sample. Data analysis was conducted using multiple linear regression with the assistance of SPSS 25 software. The results indicate that intellectual capital has no significant effect, while capital structure and company size significantly influence firm value. These findings emphasize the importance of capital structure management and company expansion strategies in enhancing firm value, while the role of intellectual capital in the mining industrystill needs to be optimized to generate a more significant impact.